Saint anything - Dessen, Sarah (New York : Viking, An imprint of Penguin Group (USA), 2015)
Sydney's charismatic older brother, Peyton, has always been the center of attention in the family but when he is sent to jail, Sydney struggles to find her place at home and the world until she meets the Chathams, including gentle, protective Mac, who makes her feel seen for the first time.
Keywords: Family problems -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Self-perception -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction